2020
DOI: 10.1111/pedi.12975
|View full text |Cite
|
Sign up to set email alerts
|

School‐aged children with type 1 diabetes benefit more from a coping skills training program than adolescents in China: 12‐month outcomes of a randomized clinical trial

Abstract: Background: Managing type 1 diabetes can be challenging, especially for youth, so there is a need for effective interventions to help youth live with diabetes.Objective: To determine the efficacy of a coping skills training (CST) program for Chinese youth with type 1 diabetes and to explore whether the efficacy of the program was different for school-aged children than for adolescents with type 1 diabetes.Methods: A total of 100 youth with type 1 diabetes aged 8 to 20 years were randomly placed in either an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
79
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(81 citation statements)
references
References 32 publications
1
79
0
1
Order By: Relevance
“…Pyatek et al 58 did not distinguish QoL outcomes by diabetes type; therefore, these results were not included in this portion of the review. Guo et al 60 reported significant increases in the QoL outcomes in a school-age intervention cohort of children with T1DM ( P = .016) but did not observe these effects in adolescents. Mayer-Davis et al, 63 demonstrated greater increases in self-reported QoL by adolescents in the intervention group compared to the control ( P = .009).…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…Pyatek et al 58 did not distinguish QoL outcomes by diabetes type; therefore, these results were not included in this portion of the review. Guo et al 60 reported significant increases in the QoL outcomes in a school-age intervention cohort of children with T1DM ( P = .016) but did not observe these effects in adolescents. Mayer-Davis et al, 63 demonstrated greater increases in self-reported QoL by adolescents in the intervention group compared to the control ( P = .009).…”
Section: Resultsmentioning
confidence: 94%
“…Participants allocated to control groups in most retained reports received usual or standardized care (n =14), 43 -45,53 -56,60 -62,63,65 -67 which typically consisted of routine visits with health care providers every 3 months. However, as opposed to usual care, the remaining 5 studies used a waiting list control group (n = 1), 64 control groups receiving diabetes education (n = 2), 59,68 or attention control groups (n = 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study group comprised 122 adolescents who were recruited as part of baseline assessment in a randomized controlled trial designed to assess the efficacy of a coping skills training program for Chinese adolescents with T1D (Guo et al, 2020). The eligibility requirements for enrollment were as follows: aged 10-18 years, diagnosed with T1D and receiving insulin treatment for at least 6 months, and the ability to speak and write Chinese.…”
Section: Samplementioning
confidence: 99%